Perioperative circulating tumor DNA enables the identification of patients with poor prognosis in upper tract urothelial carcinoma. Issue 5 (24th March 2022) - Nakano, Kosuke; Koh, Yoko; Yamamichi, Gaku; Yumiba, Satoru; Tomiyama, Eisuke; Matsushita, Makoto; Hayashi, Yujiro; Wang, Cong; Ishizuya, Yu; Yamamoto, Yoshiyuki; Kato, Taigo; Hatano, Koji; et al.
Abstract: Perioperative systemic chemotherapy improves the prognosis of upper tract urothelial carcinoma (UTUC). The first objective of this study was to verify whether perioperative circulating tumor DNA (ctDNA) analysis using a pan‐cancer gene panel and next‐generation sequencing could identify patients with poor prognosis who require perioperative chemotherapy. Second, we investigated whether ctDNA is useful for minimal residual disease (MRD) detection and treatment monitoring in UTUC. This study included 50 patients with untreated UTUC, including 43 cases of localized UTUC. We performed targeted ultradeep sequencing of plasma cell‐free DNA (cfDNA) and buffy coat DNA and whole‐exome sequencing of cancer tissues, allowing exclusion of possible false positives. We attempted to stratify the prognosis according to the perioperative ctDNA levels in patients with localized UTUC. In patients with metastatic UTUC, ctDNA was evaluated before, during, and after systemic treatment. In total, 23 (46%) of 50 patients with untreated UTUC were ctDNA positive, and 17 (40%) of 43 patients with localized UTUC were ctDNA positive. Of the detected  TP53  mutations, 19% were false positives due to clonal hematopoiesis of indeterminate potential. Among preoperative risk factors, only the preoperative ctDNA fraction>2% was a significant and independent risk factor associated with worse recurrence‐free survival (RFS). Furthermore, the existence of ctDNA early points after the operation was significantly associated with worse RFS, suggesting the presence of MRD. ctDNA also showed a potential as a real‐time marker for systemic therapy in patients with metastatic UTUC. Detection of ctDNA may indicate potential metastasis and guide decisions on perioperative chemotherapy. Abstract : In this study, we performed ultradeep sequencing of cell‐free DNA (cfDNA) in the plasma of 50 patients with untreated upper tract urothelial carcinoma (UTUC), of whom 23 (46%) were circulating tumor DNA (ctDNA) positive. Among the preoperative risk factors, only a preoperative ctDNA proportion >2% was found to be a significant and independent risk factor associated with worse recurrence‐free survival (RFS). Furthermore, the presence of ctDNA in the early postoperative period was significantly associated with worse RFS, suggesting the presence of minimal residual disease.